Refining Cheap-Talk Equilibria - Steven A. Matthews; M. Okuno-Fujiwara; Andrew Postlewaite (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1990)
Several conceptual points are made concerning communication in games of asymmetric information. Equilibrium refinements of Sender-Receiver cheap-talk games that are based on he concept of a putative equilibrium, and which rely on the presence of a rich language with literal meanings, are discussed. Three nested criteria are proposed: strong announcement-proofness, announcement-proofness, and weak announcement-proofness.
Keywords: 330